(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Internet andCommunication Technologies are transforming education, taking it out of thetraditional classroom and making it open, affordable and dynamic. Universities,publishers, corporate and individual lecturers are creating online courses. Acourse consists of video lectures, electronic study notes, online tests andassignments. Anyone who wishes to learn may enroll in these courses, take thelessons, complete the tests and assignments, and receive a certificate uponsuccessful completion of the course. These Massive Open Online Courses (MOOCs)are making world class higher education available to all those who wish tolearn, regardless of age, location or educational background. Education faces anumber of challenges worldwide. Over 366 million youth are unenrolled incolleges. College education is growing more expensive. Many institutions faceshortage of qualified faculty members, funding and infrastructure. Educationover the internet can address many of these issues. Online classes arescaleable – a class of 50 can be expanded to teach 50,000. Teaching andlearning over the internet can be done at a fraction of the cost of traditionalclassroom teaching. Flexibility, mobility, use of multimedia technologies,constant syllabus revision, collaboration and interactive discussions giveonline education an advantage. This is still an evolving field. New partnerships,innovations and technological advances are revolutionizing teaching andlearning, and clearly, online education is an integral part of the future ofeducation. India presents one of the largest educationsystems in the world showing an extensive network of more than 1 millionschools and higher education organizations. As per some surveys, more than halfof the country’s population falls in the target market for education and alliedservices. There are many institutions competing with each other to providee-learning technologies in India. They have roped in many technologicaldevelopments to felicitate their distance education branch. Many new entrantshave been noticed in the market providing students with an opportunity to widentheir horizons of knowledge and offer a wide array of Distance Learning Coursesin India. Thus in this paper we have tried to come with the comparison ofonline education system & compared to traditional classroom learning and inrelation to individual student needs, perceptions, and learning outcomes inIndian environment.